The relation between narcissism and aggression: A meta‐analysis. Issue 4 (1st November 2021) - Du, Tianwei V.; Miller, Joshua D.; Lynam, Donald R.
Abstract: Objective: Narcissism is a complex, hierarchical construct that can be studied at the one, two, or three factor levels with different components within each level having their own unique nomological networks. The manner in which narcissism—both broadly and narrowly construed—is linked to aggression is important to understand given longstanding clinical and empirical observations of a link between the two and the critical implications of aggression. Methods: The current preregistered meta‐analysis ( k  = 118) took a novel methodological approach in exploring the association between the three levels of narcissism (i.e., global construct level, dual‐dimension level, trifurcated level) and three indices of aggression (i.e., general, proactive, reactive). Results: Results revealed that the global construct of narcissism shows a moderate positive association with different indices of aggression. Vulnerable narcissism associated strongly and positively with reactive aggression and general aggression. At the trifurcated level, interpersonal antagonism associated positively with all indices of aggression, agentic extraversion associated negatively with all indices of aggression, and narcissistic neuroticism associates positively with general and reactive aggression. Conclusion: The study highlighted the importance of studying narcissism, and potentially other personality profiles, at a finer‐grained level to better understand crucial psychological processes associated with the construct of interest.